Empirical Distribution of Stock Returns of Southeast European Emerging Markets - Naumoski, Aleksandar; Gaber, Stevan; Gaber Naumoska, Vasilka (University of Tourism and Management in Skopje, 2017)
The assumption of the normal distribution of equity returns, which is the most common in the financial economics theory and applications, is clearly rejected by much empirical evidence. As it is found in many other studies, here we also confirm that the stock returns have leptokurtic distribution and skewness, which in most of the Southeast European (SEE) markets is negative. This paper investigates if there is any distribution that is an optimal fit for the stock returns in the SEE region. Using daily, weekly and monthly data samples for a period of five years of ten Southeast European emerging countries, we applied Anderson-Darling test of Goodness-of-fit. We clearly reject the normal distribution for all data samples and in all cases. We found that the daily stock returns are best fitted by the Johnson SU distribution. For the weekly and monthly stock returns there is not one predominant, but many distributions can be considered a best fit.
Keywords: Goodness-of-fit test, Anderson-Darling test, Johnson SU distribution